Variations of oxidative stress, inflammation and angiogenesis markers during an annual training cycle of elite level female waterpolo players - Varamenti, E. (Universität Thessaloniki, 2012)
Elite water polo athletes in order to respond to the demands of the sport undergo heavy training programs throughout the season. Especially in our country, due to the development that women's water polo has been shown the last decade (2nd position, Athens Olympics 2004, 1st position World Championship, China 2011), the female players must participate in series of training and games throughout the year with minimum time for recovery. The purpose of this survey was to record this strain and fatigue of these athletes through the monitoring of specific markers of oxidative stress, inflammation and angiogenesis. The participants were the same time basic members of a Greek National League club and of women`s Greek National Waterpolo Team. The biomarkers were evaluated in four distinct phases of an athletic season a) the preseason training period in September (phase T1), b) the championship in November (phase T2), c) the second round of the championship in February (phase T3) and d) during the play-offs in April (phase T4). The evaluated parameters were: a) for oxidative stress and redox status: GSH, GSSG, TBARS, PC, CAT, TAC, b) for inflammation: MCP-1, IL-10, adiponectin, c) for angiogenesis: endoglin, d) for biochemical markers: hematological markers (WBC, RBC, HBG, HCT, iron, ferritin, etc), metabolites (glucose, total cholesterol, LDL, HDL, urea, uric acid, creatinine), enzymes (CK, AST, ALT), hormones (cortisol, testosterone) and trace (K, Na, Mg). The main findings of this study suggest that the degree of oxidative stress and inflammatory response vary throughout the year in elite water polo athletes. The response of oxidative stress was increased, while the volume of training and intensity increased as the athletes went through from preparation period (preseason) to the play-offs. Conversely, the inflammatory response appeared reduced when athletes approached the time of the play-offs, where tapering and maximizing performance are the main goals. Additional, significant changes were recorded in diverse training phases for some hematological markers, metabolites, hormones and traces (ferritin, T/C ratio, creatinine, uric acid, electrolytes). These changes should be seriously taken in consideration by coaches in the formation of suitable training programs. In each training phase sport scientists have evaluate and reshape their programs according to the underlying condition of athletes in order to maintain their health and maximize their performance.